Calcium oscillations in pituitary gonadotrophs: comparison of experiment and theory. - Li, Y X (1994)
We have developed a mathematical model that describes several aspects of agonist-induced Ca2+ signaling in single pituitary gonadotrophs. Our model is based on fast activation of the inositol 1,4,5-trisphosphate (InsP3) receptor Ca2+ channels at low free cytosolic Ca2+ concentration ([Ca2+]i) and slow inactivation at high [Ca2+]i. Previous work has shown that these gating properties, when combined with a Ca(2+)-ATPase, are sufficient to generate simulated Ca2+ oscillations. The Hodgkin-Huxley-like description we formulate here incorporates these different gating properties explicitly and renders their effects transparent and easy to modulate. We introduce regulatory mechanisms of channel opening which enable the model, both in the absence and in the presence of Ca2+ entry, to give responses to a wide range of agonist doses that are in good agreement with experimental findings, including subthreshold responses, superthreshold oscillations with frequency determined by [InsP3], and nonoscillatory "biphasic" responses followed occasionally by small-amplitude oscillations. A particular added feature of our model, enhanced channel opening by reduced concentration of Ca2+ in the lumen of the endoplasmic reticulum, allows oscillations to continue during pool depletion. The model predicts that ionomycin and thapsigargin can induce oscillations with basal [InsP3] and zero Ca2+ entry, while Ca2+ injection cannot. Responses to specific pairings of sub- or superthreshold stimuli of agonist, ionomycin, and thapsigargin are also correctly predicted. Since this model encompasses a wide range of observed dynamic behaviors within a single framework, based on well-established mechanisms, its relevance should not be restricted to gonadotrophs.